Bond graph modelling of a 4-parameter photovoltaic array. Issue 3 (4th May 2018) - Villa-Villaseñor, Noé; Galindo-Orozco, René
ABSTRACT: A new model for simulating photovoltaic (PV) systems is presented. Bond Graph modelling is used as a basis technique. The proposed model allows prediction of generated energy under nonstandard conditions of temperature and irradiance. The proposed model is based on a 4-parameters model of the equivalent circuit of one diode. The proposed model has the property of being able to simulate the behaviour of a given PV module based only on information provided in the manufacturer datasheet. The proposed model also allows studying the effect of partial shading. As an advantage over other existing models of PV systems, the proposed model presents an extensive interconnection capacity. This feature allows simultaneous simulation with other subsystems to study the overall operation. For purposes of experimental validation of the proposed model, the construction of aV − I tracer based on MOSFET that acts as a variable load is performed. The hardware control and reading of the curves are made using a data acquisition board.